White matter lesions reduce number of brain metastases in different cancers: a high-resolution MRI study - Berk, Benjamin-Andreas; Nagel, Sandra; Hering, K.; Paschke, S.; Hoffmann, Karl-Titus; Kortmann, Rolf-Dieter; Gaudino, Chiara; Seidel, Clemens (Journal of neuro-oncology, 2016)
Brain metastases are major complications of common cancers. Tumor type and proneness to the CNS are thought to define the number and size of brain metastases. It is not known if intrinsic vascular factors can also have an effect. Restricted perfusion due to cerebral small vessel disease is frequent in elderly patients and causes white matter lesions (WML). The aim of this analysis was to evaluate a possible negative effect of WML and patient age on the number and size of brain metastases (BM) of different tumor entities. Pre-therapeutic 3 T brain magnetic resonance imaging (MRI) of 200 patients with BM were analyzed. Location, size and number of BM (NoM) were determined. T2 hyperintensive WML were scored according to Fazekas-Score (grade I-III). Patients with WML grade 1 (NoM: 5.59; p = 0.009) and grade 2 (NoM: 3.68; p = 0.002) had significantly less BM than patients without WML (NoM: 6.99). This effect was present in subgroups of different tumors: NSCLC (p = 0.05), other tumors than NSCLC (p = 0.048). Age (≤65 or >65 years) was positively correlated with the degree of WML but not with number (pNoM = 0.832) or mean diameter (pmDM = 0.662) of brain metastases. While patient age did not appear to be relevant, increasing WML were associated with lower number of brain metastases in different tumor types.